Back Cover: Graphene Oxide Catalyzed C−H Bond Activation: The Importance of Oxygen Functional Groups for Biaryl Construction (Angew. Chem. Int. Ed. 9/2016). Issue 9 (2nd February 2016) - Gao, Yongjun; Tang, Pei; Zhou, Hu; Zhang, Wei; Yang, Hanjun; Yan, Ning; Hu, Gang; Mei, Donghai; Wang, Jianguo; Ma, Ding
Abstract : A heterogeneous, inexpensive, and environmentally friendly graphene oxide catalytic system can be used for the C−H bond arylation of benzene for the synthesis of biaryl compounds. In their Communication onpage 3124 ff., J. Wang, D. Ma, and co‐workers show that added K +  ions are immobilized by oxygen‐containing groups at the defect sites of the graphene oxide catalyst, which is essential for the catalytic activity.